2004
DOI: 10.1186/1472-6882-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative medical therapies for chronic low back pain: What treatments are patients willing to try?

Abstract: BackgroundAlthough back pain is the most common reason patients use complementary and alternative medical (CAM) therapies, little is known about the willingness of primary care back pain patients to try these therapies. As part of an effort to refine recruitment strategies for clinical trials, we sought to determine if back pain patients are willing to try acupuncture, chiropractic, massage, meditation, and t'ai chi and to learn about their knowledge of, experience with, and perceptions about each of these the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
101
1
9

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 6 publications
2
101
1
9
Order By: Relevance
“…In a study conducted with the participation of 31.044 adults in United States, Barnes et al (2004) determined that the usage rate of the complementary methods for the last year has been 36% and back pain and lumbago come first with 16.8% and neck pain comes third with 6.6% in terms of usage reasons of the complementary methods . Sherman et al (2004) have stated that 24% of the patients with chronic lumbago used massage therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted with the participation of 31.044 adults in United States, Barnes et al (2004) determined that the usage rate of the complementary methods for the last year has been 36% and back pain and lumbago come first with 16.8% and neck pain comes third with 6.6% in terms of usage reasons of the complementary methods . Sherman et al (2004) have stated that 24% of the patients with chronic lumbago used massage therapy.…”
Section: Introductionmentioning
confidence: 99%
“…'nın yapmış olduğu çalışmada disk hernili hastaların %15.2'sinin, Kıyak ve ark. tarafından yapılan çalışmada ise disk hernili hastaların sadece %5.1'inin TİSU olarak masajı tercih ettiği saptanmıştır [13,[21][22][23].…”
Section: Discussionunclassified
“…Bulgumuza benzer şekilde aynı konuda yapılmış diğer çalışmalarda da hastaların sosyo-demografik özellikleri ile TİSU kullanımı arasında anlamlı bir ilişki bulunmamıştır [13,22].…”
Section: Discussionunclassified
“…Those few that have asked participants about their willingness to pay for massage therapy have shown conflicting results. For instance, chronic low back pain patients in the U.S. indicated that they would only be willing to receive massage therapy if they did not have to pay out of pocket while questionnaires completed in the UK indicated that 76% of 162 cancer patients were willing to pay out of pocket for massage therapy [32]. In both studies, potential out of pocket amounts were not specified.…”
Section: Introductionmentioning
confidence: 99%